From creative thinking to scientific principles in clinical practice. Issue 1 (January 2021) - Lambert, Simon; Mischler, Dominic; Windolf, Markus; Regazzoni, Pietro; Dell'Oca, Alberto Fernandez; Gueorguiev, Boyko; Varga, Peter
Highlights: Stephan Perren revolutionised the comprehension of fracture healing by elucidating his Strain Theory, which he described as a study of the 'inductor' of bone fracture healing, as opposed to the chemical events that followed, which he termed the 'effectors' of bone healing. The application of the principles of his studies into the mechanobiology of bone and bone fracture to a learning framework for clinicians became of increasing interest over his career, and paralleled developments in adult educational psychology and the technology to deliver novel ideas in active and passive learning environments. Among his many collaborations which resulted in revolutionary changes in how those principles could be learnt, Perren enjoyed the evolution of the AO Skills Lab from the Playground concept; the later great work of the ICUC project with his friends Pietro Regazzoni and Alberto Fernandez Dell'Oca; and the nascence of the OSApp, a novel FE-based 'virtual playground' in which students of musculoskeletal trauma could enjoy a self-directed learning environment. Abstract: Stephan Perren's contributions to the understanding and application of the principles of bone pathobiology, healing, and fracture fixation to clinical care remain as a lasting legacy of a great creative mind. Less well appreciated perhaps were his important contributions to the dissemination and practical application of those principles through the use of technology as applied to the learning environment. This paper describes and pays tribute to a series of initiatives in which Perren was a leading mentor and collaborator in the development of methods and instruments through which the principles of bone mechano-pathobiology could be translated through active learning environments into the practical world of clinical musculoskeletal traumatology.